Peran Public Relation The Sunan Hotel Solo terhadap Peningkatan Brand Awareness : (Studi Kasus Event Srawung Sunan) - Ananditho Hernando Syahputra Ariyanta; Agus Solikhin; Afiefah Sulistiyowati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the role of Public Relations at The Sunan Hotel Solo in increasing brand awareness through the Srawung Sunan event. The tourism and hospitality industry in Solo has experienced rapid growth, supported by high-quality services and effective promotional strategies. Public relations, brand awareness, and event management are essential elements in maintaining the sustainability of the hotel business. As a four-star hotel strategically located in Solo, The Sunan Hotel Solo actively organizes various events to strengthen its brand image and public engagement. This research aims to identify the activities and strategies carried out by the Public Relations department in enhancing brand awareness through the Srawung Sunan event. The study employed a qualitative method with a case study approach. Data were collected through interviews with five informants from the Public Relations department and the Food and Beverage Sales Manager of The Sunan Hotel Solo. Data triangulation methods, including observation, interviews, and documentation, were used to ensure validity. The findings indicate that the Public Relations team played a significant role in the preparation and implementation of the event, including coordination with local districts, promotional activities, and collaboration with participants, which successfully strengthened the hotel’s branding strategy and public image.